Comparison of Four Diagnostic Methods for Detection and Relative Quantification of Haemonchus contortus Eggs in Feces Samples - Ljungström, Sara; Melville, Lynsey; Skuce, Philip John; Höglund, Johan (Frontiers in Veterinary Science, 2018)
We compared four methods for identification of H. contortus eggs. With increased trade in animals within and between countries and continents, it has become important to correctly identify H. contortus eggs in faecal samples. To validate the outcome of diagnostic tests, sheep faeces (n=38) were collected from naturally infected flocks in Sweden. Sub-samples were analysed with: a) McMaster egg counting; b) differential counting of eggs after staining with peanut agglutinin (PNA); c) detection of DNA following amplification by real-time quantitative polymerase chain reaction (qPCR); and d) loop-mediated isothermal amplification (LAMP). Differences between similar tests (microscopic, molecular) and standard deviation (±SD) were analysed with Bland-Altman plots and Spearman rank correlation. Strongylid egg counts ranged from 200 to 12,100 eggs per gram (epg) (mean epg ± SD = 1,278 ±2,049). Microscopy showed presence of H. contortus eggs in 27 (73%) unstained samples and in 28 (76%) samples stained with PNA, whereas 29 samples (78%) tested positive in LAMP and 34 (91%) in qPCR analysis. The cycling threshold (Ct) values with LAMP ranged between 13 and 38 (mean ± SD = 21±7), and those in qPCR between 25 and 49 (mean ± SD = 33±6). In the LAMP and qPCR analyses, seven (19%) and three (8%) samples, respectively, had a cycle threshold (Ct) >35, whereas no reactions were observed in eight (22%) and three (8%) samples, respectively. There was good agreement between the diagnostic tests based on microscopic examination and DNA detection, although the molecular tests were more sensitive. The bias between the microscopy methods (-4.2 ±11) was smaller than for the molecular tests (-9.8 ±10). The observed ranking in terms of test sensitivity was: McMaster counting by conventional microscopy < PNA < LAMP < qPCR. In conclusion, H. contortus can be identified by McMaster counting, without major mistakes regarding false positive results. However, molecular methods provide the capacity to diagnose H. contortus eggs with increased accuracy. This is essential when animals are investigated in quarantine or in studies evaluating anthelmintic treatment efficacy. These methods could also be applied to faecal samples from wildlife to investigate nematode transmission between wildlife and livestock.